Editorial (International Journal of Business Innovation, 2023)
Welcome to the International Journal of Business Innovation! As we set sail into the fourth and final issue of the second volume, we take a moment to ponder the remarkable journey we've shared. With great pride, we commemorate the strides we've taken together in advancing cutting-edge research and cultivating innovation within the business realmDespite being in our initial years, our journal has already established itself as a platform for groundbreaking ideas and transformative insights. We have had the privilege of publishing exceptional research articles that have not only contributed to the advancement of knowledge but have also made a tangible impact on the business community. Our commitment to quality, rigor, and relevance has garnered attention from scholars, practitioners, and industry leaders alike, solidifying our position as a trusted source of knowledge and inspiration.In this editorial, we aim to showcase the remarkable success that we have achieved thus far, highlighting the exceptional contributions of our esteemed authors, reviewers, and editorial board members. Their dedication and expertise have played a pivotal role in shaping the journal's reputation and elevating it to new heights. We are immensely grateful for their unwavering support and collaboration.In the dynamic landscape of 21st-century workstyles, the importance of Emotional Intelligence (EQ) in leadership cannot be overstated. The article, "Emotional Intelligence: Why It Matters in Change Leadership and Innovation in the 21st Century Styles of Work," delves into the critical role EQ plays in achieving organizational goals amidst the uncertainties of the global business environment. Long dismissed in earlier studies as an impediment to rational decision-making, emotions are now recognized as a key determinant in what sets effective leaders apart. Drawing from Daniel Goleman's EQ theory, our research, based on responses from 69 leaders in Australian public and private sectors, employs an evidence-based approach to shed light on the relationship between EQ and leadership high performance. The findings highlight the significant influence of emotional self-awareness, self-motivation, empathy, and overall EQ on leadership behavior. This study not only contributes to a deeper understanding of EQ's role in superior leadership but also carries implications for leadership search firms and human resource practitioners seeking to cultivate and identify leaders poised for success in the ever-evolving business landscape. As we navigate the complexities of modern leadership, embracing and harnessing emotional intelligence emerges as a cornerstone for achieving excellence in organizational leadership.In the latest exploration of Nistor and Filip, they scrutinize a pertinent question: "Is European Fund's implementation subject to slipup for emerging countries' approach?" The study, grounded in a holistic approach, delves into the realm of non-refundable European funds (NREF) and their intricate dynamics. By anchoring our investigation in the outcomes of an operational audit, which sheds light on weaknesses and errors, and emphasizing the pivotal role of follow-up operations in remediation, the authors conduct a longitudinal examination spanning from 2008 to 2020, focusing on Romania—a former communist country that has transitioned into a European Union member. Through a comprehensive theoretical and empirical framework, our findings paint a nuanced picture of the fluctuating evolution of European funds' implementation across various operational programs in Romania over the past 22 years. These insights not only provide a valuable reference for Eastern European countries navigating the terrain of European Funds but also spotlight the unique challenges arising from the lack of governmental experience, shifting legislation, and a nuanced understanding of Eastern European culture by the EU. Importantly, our research underscores the positive trajectory marked by improved familiarity with non-reimbursable funds and the discernible effects of follow-up operations in recent years, signifying a positive trend in addressing the challenges and potential pitfalls faced by emerging countries in their utilization of European funds.In the ever-evolving landscape shaped by Industry 4.0 and the emerging wave of Industry 5.0, the role of the professional accountant stands at the forefront of transformation. The article, "Impact of Industries 4.0 and 5.0 on the Professional Accountant and Auditor's Integrated Thinking Skills Skillset and Other Pervasive Skills," delves into the profound changes these industrial revolutions have wrought upon the business world and, more specifically, the evolving expectations placed on professional accountants. Recognizing that the changing demands necessitate an altered and enhanced skillset, with a heightened emphasis on pervasive skills, this study aims to dissect the impact of these technological shifts on the requisite skills for professional accountants. The authors spotlight the imperative for integrated thinking skills, acknowledging that the modern business landscape is replete with complex challenges that demand a multidisciplinary approach, drawing from both financial and non-financial realms, internal and external information. Through an archival research design, this study underscores how Industry 4.0 and Industry 5.0 have significantly altered the professional accountant's role, necessitating a new, pervasive skillset, where integrated thinking skills emerge as a linchpin for success in navigating the intricacies of the contemporary financial landscape. As authors stand at the intersection of technology and accounting, understanding and cultivating these skills become paramount for professionals to thrive in an era of unprecedented change.The article “Fintech Development, RegTech and Financial Institutions in Ghana: Starting with The Regulatory Sandbox" delves into the multifaceted dimensions of Fintech development in Ghana, intricately dissecting policy, legal, and technical aspects that shape this dynamic sector. The spotlight is on Ghana's regulatory sandbox and Fintech laws, scrutinizing key elements such as consumer protection, data protection, and cybersecurity. The study provides an in-depth analysis of the regulatory evolution and its profound impact on the Fintech landscape, illuminating the symbiotic relationship between financial regulators and Fintech entities in leveraging technology for supervision and compliance. As we navigate through challenges and assess industry stability, the article meticulously evaluates the transformative potential of RegTech in reshaping Ghana's financial regulatory model. With a multimodal approach, this study not only presents a comprehensive analysis of the current state of Fintech in Ghana but also offers insightful policy recommendations to fortify the financial RegTech framework. It underscores the critical need for a well-coordinated approach to Fintech policy development and implementation, emphasizing the importance of adaptability and foresight in fostering a resilient and innovative financial ecosystem in Ghana.In conclusion, we urge readers to delve into the wealth of knowledge presented in this issue of our journal. The diverse array of articles spans a broad spectrum of topics, illuminating innovative research, groundbreaking discoveries, and thought-provoking perspectives. Our heartfelt appreciation goes to the authors who have generously shared their expertise and insights, thereby enhancing the collective knowledge of our scholarly community.As we progress, we extend an invitation to all readers to actively contribute to the growth and success of the International Journal of Business Innovation. Whether through the submission of research articles, serving as a valued reviewer, or engaging in meaningful discussions, your contributions are indispensable in shaping the forthcoming issues. Your distinct perspectives and experiences promise to enrich the ongoing dialogue and propel further advancements in our respective fields.We eagerly anticipate your active participation and valuable contributions in the upcoming issues of our journal as we endeavor to push the boundaries of knowledge and make impactful strides in the realm of business innovation. Thank you for your steadfast support, and we eagerly look forward to your continued involvement with the International Journal of Business Innovation.
Keywords: Editorial